The effects of taping, stretching, and joint exercise on hip joint flexibility and range of motion - Choi, Jung-Hyun (J Phys Ther Sci, 2016)
[Purpose] This study aimed to examine the effects of joint exercise, taping, and stretching on hip joint flexion, flexibility, and range of motion. [Subjects and Methods] Forty-five college students in their 20s were randomly assigned and equally divided into three groups, as follows: a stretching group, a taping and exercise group, and an exercise group. Changes in trunk range of motion and hip joint flexibility of the three groups were measured before and after the intervention. [Results] Comparison between flexibility before and after the intervention revealed statistically significant changes in all three groups. Moreover, the evaluation of joint range of motion after the intervention showed that there were statistically significant changes in all three groups. [Conclusion] Taping, stretching, and joint exercise are considered effective for the increase in flexibility and joint range of motion.